Analisis Pemberian Kompensasi yang Berdampak Terhadap Turnover Intention pada Karyawan Bagian Produksi, Studi Kasus pada Sebuah Perusahaan Garmen di Kota Bandung - Juddy Prabowo; Cecilia Natasya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to find out the impact of compensation on turnover intention on employees of the production department, a case study of a garment company in Bandung City. The research uses methods of qualitative analysis and data collection methods with interviews, documentation and library research. This research population is the whole of employees associated with a garment company in the city of Bandung. The validity and reliability tests in this study use triangulation. There are three processes of data analysis techniques: data reduction, data presentation, conclusion and verification. The result of this study is that the analysis of compensation is a factor causing turnover intention. It can be said that compensation to employees of the production part of a garment company in Bandung City is in the bad category. Results have been obtained which indicate that the employee's current compensation is not sufficient to meet employee needs. This is because of the company's lack of attention in giving a fair and decent salary to every employee. Besides that the turnover intention on employees of the production part of a garment company in Bandung City is in the high category. The result was that as much as 70% (7 employees) had a desire to leave the company to get a better job. To conclude, the company has violated a number of state rules relating to fair pay rules that violate the Regulations of the Minister of Employment of the Republic of Indonesia No. 18 Year 2022 Article 2 Paragraph (1), and violates the accuracy of pay timing of section 61 of the Government Regulations (PP) No. 36 Year 2021 On Employment.